Thunderheart - Apted, Michael; Fred, Ward.; Graham Greene; Sam Shepard; Val Kilmer (USA Tribeca Productions, 1992)
An FBI man with Sioux background is sent to a reservation to help with a murder investigation, where he has to come to terms with his heritage. Slowly he rejects the intimidating tactics of his fellow FBI agents, who are not so interested in solving the crime as covering up an incriminating situation with the locals, and as he becomes more tuned to his heritage, the locals begin trusting him. Based on actual Reservation occurrences of the '70s.
An FBI man with Sioux background is sent to a reservation to help with a murder investigation, where he has to come to terms with his heritage...
John Fusco
Language(s): English, French
Subtitle(s): English, French, Italian, Spanish, Arabic, Greek, Hindi, Turkish
Keywords: Crime